Trends and approaches to reorganization of urban environment - Sedin, Volodymyr; Kovalov, Viacheslav; Kravchunovska, Tetiana; Nechepurenko, Daria (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article describes the standards of urban environment reorganization, which are oriented to the effective use of land resourcesand the load distribution for urban transport infrastructure, a high degree of functional diversity. The authors haveanalyzed the approaches and trends of the urban environment transformation, based on the concept of the compact cities formation.The authors determined specific features of the urban industrial environment transformation different types dependingon the degree and direction of the objects modification. In the conditions of land plots shortage, redevelopment projectsprovide an opportunity to renew the urban environment, to solve transport problems, and to find the potential for buildingnew objects.
Keywords: reorganization; redevelopment; reconstruction; revitalization; renovation